Optimasi Kinerja Sensor Ultrasonik pada Prototype Sistem Monitoring Slot Parkir - Fitriani, Fitriani; Saenong, Andi; Idris, Mochammad Agus; Justam, Justam (TIN: Terapan Informatika Nusantara, 2025)
The growth of private vehicles in urban areas poses significant challenges in managing parking spaces efficiently and accurately. The Internet of Things (IoT) technology offers a promising solution for developing an automated parking slot monitoring system based on sensors. This study aims to optimize the performance of ultrasonic sensors by evaluating two different installation positions: at the rear (Scenario A) and above (Scenario B) the parking slot. The research was conducted using an experimental approach with a miniature prototype, where data were collected and evaluated based on detection accuracy. The results showed that Scenario B achieved an accuracy of 85%, whereas Scenario A reached only 55%, with a 30% accuracy difference. These findings indicate that sensor placement greatly influences system performance in detecting the presence of vehicles. This study provides a significant contribution to the development of more accurate and efficient IoT-based automated parking systems.